An Incidentally Detected Venous Malformation of the Uterine Cervix: Case Report - Yeşim Bayoğlu Tekin; Recep Bedir; Emine Seda Güvendağ Güven (Gynecology Obstetrics & Reproductive Medicine)
Venous malformations of the uterine cervix are extremely rare. Most lesions are asymptomatic and incidental, however sometimes, they may present with abnormal vaginal bleeding. We aimed to describe a case of venous malformation of the uterine cervix and discuss the differential diagnosis and clinical management of this entity.